Modern mythology - Lang, Andrew (Longmans, Green, and co., 1897)
Introduction.--Recent mythology.--The story of Daphne.--The question of allies.--Mannhardt.--Philology and Demeter Erinnys.--Totemism.--The validity of anthropological evidence.--The philological method in anthropology.--Criticism of fetishism.--The riddle theory.--Artemis.--The fire-walk.--The origin of death.--Conclusion.